Codon usage bias analysis of the WRKY gene family in Musa acuminata - Sun, Jiaman; Zhang, Ji; Zhang, Jinzhong; Ferguson, Brett J.; Chen, Andrew (Frontiers in Genetics, 2025)
Codon usage bias (CUB), a universal evolutionary phenomenon, reflects selective pressures shaping genome adaptation. The WRKY transcription factor family plays a pivotal role in regulating plant responses to physiological and biochemical stresses. This study investigates CUB patterns in 151 WRKY transcription factors of Musa acuminata ‘Guijiao 9′, a banana cultivar exhibiting resistance to Fusarium wilt Tropical Race 4 (TR4), to elucidate evolutionary drivers of stress adaptation. The codons of these transcription factors were selected based on their expression from RNA-Seq data. The average GC content of MaWRKY genes was 56.55%, with a GC3 content of 62.23%, indicating a preference for G/C-ending codons. Among the codons, 26 were identified as high frequency, with 22 ending in G or C. The high effective number of codons (ENC) values (35.03–60.14) suggested weak CUB. ENC-plot, PR2 bias plot, and neutrality analysis revealed that both natural selection and mutation pressure contributed to the observed CUB, with natural selection being the dominant factor influencing the codon usage of MaWRKY genes in M. acuminata ‘Guijiao 9'. Fifteen optimal codons, all ending in G or C, were identified. This analysis provides a theoretical foundation for further understanding the evolutionary mechanisms of WRKY genes in Musa.